Same Scandal, Different Standards: The Effect of Partisanship on Expectations of News Reports about Whistleblowers. Issue 2 (4th March 2023) - Duncan, Megan; Perryman, Mallory; Shaughnessy, Brittany
ABSTRACT: This experiment ( N  = 591) tests whether audiences adjust their standards for what qualifies as fair journalism based the transparency of news editors, the source of the news, and the target of an accusation. In the context of a whistleblower scandal, the results suggest the relationship between the audience member's ideology and the news story publisher and target influence what details the audience thinks journalists should reveal. Additionally, we find transparency from editors can alter those perceptions.